Effects of bacterial bio-augmentation on the methane potential from facultative digestion of palm oil mill effluent and empty fruit bunch - Chin, Kit Ling; Mohd Yaakob, Nurliyana; H'ng, Paik San; Lee, Chuan Li; Go, Wen Ze; Khoo, Pui San; Raja Nazrin, Raja Ahmad; Siti Nurul Ashikin (Springer, 2019)
The methane productivity and biodegradability of facultative single- and co-digestion samples with palm oil mill wastes was evaluated on the effect of bacterial bio-augmentation. The single- and co-digestion substrates were bio-augmented with Bacillus subtillis and a methanogenic mixed culture of anaerobic microorganisms at different loading percentage. The highest methane production was recorded at 0.95 LCH4 from co-digestion sample augmented with 10% (v/v) B. subtilis while the highest methane yield of 0.7 mLCH4/g volatile solid, attained by single-digestion of palm oil mill effluent with addition of mixed methanogens at 5% (v/v). Cumulative methane production for single-digestion increased from 0.17 LCH4 to 0.32 LCH4 in response to the bio-augmentation treatment with 5% mixed methanogens. Conversely, additional mixed methanogens to co-digestion substrate resulted 75% reduction in methane production compared to non-augmented co-digestion substrate. Addition of B. subtilis into co-digestion was more beneficial than mixed methanogens due to the cellulolytic degradation ability of B. subtilis to digest the lignocellulolytic substances in empty fruit bunch.